Multiparity increases trophoblast invasion and vascular endothelial growth factor expression at the maternal–fetal interface in mice - Litwin, Silvana (2010)
To analyze immunomodulating effects related to parity status, we studied trophoblast invasion grade, placental expression and systemic concentration of VEGF and its receptor Flt-1 in normal fertile (CBA/JxBALB/c) mice and abortion-prone (CBA/JxDBA/2) H-2(d)xH-2(k) mice. BALB/c or DBA/2 mated CBA/J females were, respectively, divided into the following groups: primiparous young (3.0+/-0.5 months old); primiparous old (8.5+/-0.5 months old) and multiparous old (8.5+/-0.5 months old, with 4 pregnancies). Immunohistochemical analysis of term placentae from both multiparous groups revealed various layers of invasive trophoblast tissue, identified as cytokeratin+/vimentin- cells, in contrast to the single layer detected in the placentae of primiparous animals, indicating that multiparity increases trophoblast invasion regardless of the success of the pregnancy outcome. Invasive trophoblast tissue from primiparous CBA/JxDBA/2 placentae showed diminished VEGF expression in comparison with the normal fertile group, while both multiparous groups demonstrated high expression of VEGF in the invasive trophoblast tissue. Placental expression of Flt-1 was similar in all groups. However, the primiparous CBA/JxBALB/c group showed the highest plasma concentration of sFlt-1 at term, while both multiparous groups demonstrated low circulating levels. No differences in circulating VEGF levels were observed among the groups. These results demonstrate an increase in trophoblast invasion tissue and expression of VEGF in the maternal-fetal interface in multiparous mice compared to primiparous mice. Moreover, the placenta appears to be able to regulate the circulating levels of VEGF by releasing sFlt-1.